In vitro evaluation of a natural food supplement as inhibitors of feline herpesvirus replication - Pacini, MI; Bonaccini, P; Mazzei, M; Forzan, M (Journal of the Hellenic Veterinary Medical Society, 2024)
The feline herpesvirus (FHV) is a widely diffused and highly contagious virus that represents a common health problem in cats. It is frequently associated with diseases of different pathogenicity that can be particularly severe in young kittens determining viral pneumonia and sometimes, death. Unfortunately, there isn’t a well-defined therapeutic protocol against the virus. Several studies concerning the application of alternative treatments against herpesviruses have been performed with promising results, in both human and veterinary medicine. The present study aims to investigate in vitro antiviral effects against FHV of the commercially compound HELP-TH1 (Camon, S.p.A., Italy) mainly composed by Ganoderma lucidum, Cordyceps sinensis, and Trametes versicolor. The antiviral effect of HELP-TH1 was evaluated by the Plaque Reduction Assay and by the real time PCR quantifying and comparing the viral load of infected controls vs treated experimental samples. Our data indicate that HELP-TH1 inhibits the cytopathic effect of the virus and reduces the viral load in the experimental conditions demonstrating its antiviral effect.